Warm-up Practices in Elite Boxing Athletes: Impact on Power Output. Issue 1 (January 2017) - Cunniffe, Brian; Ellison, Mark; Loosemore, Mike; Cardinale, Marco
Abstract : Abstract: Cunniffe, B, Ellison, M, Loosemore, M, and Cardinale, M. Warm-up practices in elite boxing athletes: Iimpact on power output. J Strength Cond Res 31(1): 95–105, 2017—This study evaluated the performance impact of routine warm-up strategies in elite Olympic amateur boxing athletes and physiological implications of the time gap (GAP) between warm-up and boxing activity. Six male boxers were assessed while performing standardized prefight warm-up routines. Core and skin temperature measurements (Tcore and Tskin ), heart rate, and upper- and lower-body power output (PO) were assessed before and after warm-up, during a 25-minutes GAP and after 3 × 2 minutes rounds of sparring. Reflected temperature (Tc ) was also determined using high-resolution thermal images at fixed time-points to explore avenues for heat loss. Despite individual differences in warm-up duration (range 7.4–18.5 minutes), increases in Tcore and Tskin occurred ( p ⩽ 0.05). Corresponding increases (4.8%; p ⩽ 0.05) in countermovement jump (CMJ) height and upward-rightward shifts in upper-body force-velocity and power-velocity curves were observed. Athletes remained inactive during the 25-minutes GAP with a gradual and significant increase in Tc occurring by the end of GAP suggesting the likelihood of heat loss. Decreases in CMJ height and upper-body PO were observed after 15 minutes and 25 minutes GAP ( p ⩽ 0.05). By the end of GAP period, all performance variables had returned to pre–warm-up values. Results suggest routine warm-ups undertaken by elite boxers have acute effects on power-generating capacity. Gradual decreases in performance variables are evident with inactivity and seem related to alterations in body temperature. Considering the constraints of major competitions and time spent in air conditioned holding areas before fights, practitioners should be aware of the potential of nullifying the warm-up effects.